PAF-AH catalytic subunits modulate the Wnt pathway in developing GABAergic neurons - Livnat, Idit; Finkelshtein, Danit; Ghosh, Indraneel; Arai, Hiroyuki; Reiner, Orly (Frontiers in Cellular Neuroscience, 2010)
Platelet-activating factor acetylhydrolase 1B (PAF-AH) inactivates the potent phospholipid platelet-activating factor (PAF) and is composed of two catalytic subunits (α1 and α2) and a dimeric regulatory subunit, LIS1. The function of the catalytic subunits in brain development remains unknown. Here we examined their effects on proliferation in the ganglionic eminences and tangential migration. In α1 and α2 catalytic subunits knockout mice we noticed an increase in the size of the ganglionic eminences resulting from increased proliferation of GABAergic neurons. Our results indicate that the catalytic subunits act as negative regulators of the Wnt signaling pathway. Overexpression of each of the PAF-AH catalytic subunits reduced the amount of nuclear beta-catenin and provoked a shift of this protein from the nucleus to the cytoplasm. In the double mutant mice, Wnt signaling increased in the ganglionic eminences and in the dorsal part of the cerebral cortex. In situ hybridization revealed increased and expanded expression of a downstream target of the Wnt pathway (Cyclin D1), and of upstream Wnt components (Tcf4, Tcf3 and Wnt7B). Furthermore, the interneurons in the cerebral cortex were more numerous and in a more advanced position. Transplantation assays revealed a non-cell autonomous component to this phenotype, which may be explained in part by increased and expanded expression of Sdf1 and Netrin-1. Our findings strongly suggest that PAF-AH catalytic subunits modulate the Wnt pathway in restricted areas of the developing cerebral cortex. We hypothesize that modulation of the Wnt pathway is the evolutionary conserved activity of the PAF-AH catalytic subunits.